Molecular diagnosis of hereditary nonpolyposis colorectal cancer (Lynch syndrome) (2016)
Lynch syndrome is the most common cause of inherited colorectal cancer, totaling 5 to 8% of all the cases with high susceptibility to this type of cancer and extracolonic cancer. It is related to germinal mutations taking place at mismatch repair genes. The diagnosis of Lynch syndrome is essential for both monitoring patients with this disease and detecting asymptomatic carriers, in order to establish appropriate clinical monitoring, preventive management and genetic counselingAlthough clinical criteria have been standardized by implementing Amsterdam I and II, as well as Bethesda guidelines, the detection rate of mutations in these genes only varies between 20% and 60%.The objective of this research was to review the state of the art regarding molecular diagnosis of Lynch syndrome; thus, a review of the literature published from 1995 to 2015 in PubMed database was performed by using the criteria “lynch syndrome molecular screening”. 19 articles were selected and reviewed, and the relevant bibliography related to such articles was also reviewed.This paper presents different approaches proposed by several researchers on molecular algorithms to improve the efficiency of Lynch syndrome diagnosis.